Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the inequality [tex]\(\frac{x^2 + x - 6}{x - 7} \leq 0\)[/tex], let's go through it step-by-step.
### Step 1: Factorize the numerator
First, we factorize the quadratic expression in the numerator:
[tex]\[ x^2 + x - 6 \][/tex]
We look for two numbers that multiply to [tex]\(-6\)[/tex] and add to [tex]\(1\)[/tex]. These numbers are [tex]\(3\)[/tex] and [tex]\(-2\)[/tex]. Thus,
[tex]\[ x^2 + x - 6 = (x + 3)(x - 2) \][/tex]
### Step 2: Rewrite the inequality
Substitute the factorized form of the quadratic expression back into the inequality:
[tex]\[ \frac{(x + 3)(x - 2)}{x - 7} \leq 0 \][/tex]
### Step 3: Determine critical points
The critical points are where the numerator and denominator are zero:
1. [tex]\(x + 3 = 0 \implies x = -3\)[/tex]
2. [tex]\(x - 2 = 0 \implies x = 2\)[/tex]
3. [tex]\(x - 7 = 0 \implies x = 7\)[/tex]
### Step 4: Sign analysis
We need to analyze the signs of each factor in the intervals determined by the critical points:
- Intervals: [tex]\((- \infty, -3]\)[/tex], [tex]\((-3, 2]\)[/tex], [tex]\((2, 7)\)[/tex], [tex]\( (7, \infty) \)[/tex]
Check the sign of [tex]\(\frac{(x + 3)(x - 2)}{x - 7}\)[/tex] in each interval:
1. For [tex]\(x \in (- \infty, -3)\)[/tex]:
- [tex]\(x + 3 < 0\)[/tex]
- [tex]\(x - 2 < 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
The expression is [tex]\(\frac{(-)(-)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
2. For [tex]\(x \in [-3, 2]\)[/tex]:
- [tex]\(x + 3 \geq 0\)[/tex]
- [tex]\(x - 2 \leq 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
For [tex]\(x = -3\)[/tex]: [tex]\(\frac{0 \cdot (-5)}{-10} = 0\)[/tex], satisfies because [tex]\(\leq 0\)[/tex].
For [tex]\(x \in (-3, 2)\)[/tex]: The expression [tex]\(\frac{(+)(-)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
For [tex]\(x = 2\)[/tex]: [tex]\(\frac{- \cdot 0}{-5} = 0\)[/tex], satisfies because [tex]\(\leq 0\)[/tex].
3. For [tex]\(x \in (2, 7)\)[/tex]:
- [tex]\(x + 3 > 0\)[/tex]
- [tex]\(x - 2 > 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
The expression is [tex]\(\frac{(+)(+)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
4. For [tex]\(x \in (7, \infty)\)[/tex]:
- [tex]\(x + 3 > 0\)[/tex]
- [tex]\(x - 2 > 0\)[/tex]
- [tex]\(x - 7 > 0\)[/tex]
The expression [tex]\(\frac{(+)(+)}{+} = +\)[/tex]. Positive, not satisfying.
### Step 5: Combining intervals
The solution includes the points and intervals where the expression is less than or equal to zero:
[tex]\[ (- \infty, -3] \quad \text{and} \quad [2, 7) \][/tex]
However, we must include the endpoints [tex]\(-3\)[/tex] and [tex]\(2\)[/tex] but exclude [tex]\(7\)[/tex] since division by zero is not allowed.
### Final solution:
[tex]\[ x \leq -3 \quad \text{or} \quad 2 \leq x < 7 \][/tex]
Therefore, the correct interval is:
[tex]\[ \boxed{x \leq -3 \quad \text{or} \quad 2 \leq x < 7} \][/tex]
### Step 1: Factorize the numerator
First, we factorize the quadratic expression in the numerator:
[tex]\[ x^2 + x - 6 \][/tex]
We look for two numbers that multiply to [tex]\(-6\)[/tex] and add to [tex]\(1\)[/tex]. These numbers are [tex]\(3\)[/tex] and [tex]\(-2\)[/tex]. Thus,
[tex]\[ x^2 + x - 6 = (x + 3)(x - 2) \][/tex]
### Step 2: Rewrite the inequality
Substitute the factorized form of the quadratic expression back into the inequality:
[tex]\[ \frac{(x + 3)(x - 2)}{x - 7} \leq 0 \][/tex]
### Step 3: Determine critical points
The critical points are where the numerator and denominator are zero:
1. [tex]\(x + 3 = 0 \implies x = -3\)[/tex]
2. [tex]\(x - 2 = 0 \implies x = 2\)[/tex]
3. [tex]\(x - 7 = 0 \implies x = 7\)[/tex]
### Step 4: Sign analysis
We need to analyze the signs of each factor in the intervals determined by the critical points:
- Intervals: [tex]\((- \infty, -3]\)[/tex], [tex]\((-3, 2]\)[/tex], [tex]\((2, 7)\)[/tex], [tex]\( (7, \infty) \)[/tex]
Check the sign of [tex]\(\frac{(x + 3)(x - 2)}{x - 7}\)[/tex] in each interval:
1. For [tex]\(x \in (- \infty, -3)\)[/tex]:
- [tex]\(x + 3 < 0\)[/tex]
- [tex]\(x - 2 < 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
The expression is [tex]\(\frac{(-)(-)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
2. For [tex]\(x \in [-3, 2]\)[/tex]:
- [tex]\(x + 3 \geq 0\)[/tex]
- [tex]\(x - 2 \leq 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
For [tex]\(x = -3\)[/tex]: [tex]\(\frac{0 \cdot (-5)}{-10} = 0\)[/tex], satisfies because [tex]\(\leq 0\)[/tex].
For [tex]\(x \in (-3, 2)\)[/tex]: The expression [tex]\(\frac{(+)(-)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
For [tex]\(x = 2\)[/tex]: [tex]\(\frac{- \cdot 0}{-5} = 0\)[/tex], satisfies because [tex]\(\leq 0\)[/tex].
3. For [tex]\(x \in (2, 7)\)[/tex]:
- [tex]\(x + 3 > 0\)[/tex]
- [tex]\(x - 2 > 0\)[/tex]
- [tex]\(x - 7 < 0\)[/tex]
The expression is [tex]\(\frac{(+)(+)}{-} = \frac{+}{-} = -\)[/tex]. Negative.
4. For [tex]\(x \in (7, \infty)\)[/tex]:
- [tex]\(x + 3 > 0\)[/tex]
- [tex]\(x - 2 > 0\)[/tex]
- [tex]\(x - 7 > 0\)[/tex]
The expression [tex]\(\frac{(+)(+)}{+} = +\)[/tex]. Positive, not satisfying.
### Step 5: Combining intervals
The solution includes the points and intervals where the expression is less than or equal to zero:
[tex]\[ (- \infty, -3] \quad \text{and} \quad [2, 7) \][/tex]
However, we must include the endpoints [tex]\(-3\)[/tex] and [tex]\(2\)[/tex] but exclude [tex]\(7\)[/tex] since division by zero is not allowed.
### Final solution:
[tex]\[ x \leq -3 \quad \text{or} \quad 2 \leq x < 7 \][/tex]
Therefore, the correct interval is:
[tex]\[ \boxed{x \leq -3 \quad \text{or} \quad 2 \leq x < 7} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.